Assessment of Heart Rate Variability in Hypertensive Patients - Archana; Preeti Agarwal (Asian Journal of Medical Research, 2019)
Background: Heart rate variability (HRV) has emerged as a practical, noninvasive tool to quantitatively investigate cardiac autonomic dysregulation in hypertension. The present study was conducted to assess heart rate variability in hypertensive patients.Subjects and Methods:The present study was conducted on 45 hypertensive patients of both genders. Spectral indices of HRV such as total power (TP), normalized low frequency power (LFnu), normalized high frequency power (HFnu), ratio of low frequency power to high frequency power (LF-HF ratio), standard deviation of normal-to-normal RR intervals (SDNN), root mean square successive difference (rMSSD) and the proportion of NN50 to the total number of NN intervals (pNN50) were assessed.Results:Group I had 25 males and 20 females while group II had 23 males and 22 females. SDNN (ms) in group I was 157.2 and in group II was 146.3, rMSSD (ms) in group I was 44.5 and in group II was 38.5, pNN50 in group I was 15.4 and in group II was 10.8. LFnu in group I was 76.2 and in group II was 89.1, HFnu in group I was 57.4 and in group II was 37.6, LF/HF ratio in group I was 2.87 and in group II was 4.85.Conclusion: HRV can be used as a routine screening test to predict the future risk of hypertension at an earlier stage. There is an increased sympathetic activity and a decreased vagal tone associated with hypertension.